2020
DOI: 10.1002/mgg3.1157
|View full text |Cite
|
Sign up to set email alerts
|

Role of Helicobacter pylori infection in the manifestation of old age‐related diseases

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes. AbstractHelicobacter pylori is one of the most prevalent infection worldwide. It affects individuals of different age groups. Elderly people tend to resist eradication treatment and worsening of infection can lead to several gastric and non-gastric pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 111 publications
2
18
0
Order By: Relevance
“…A meta-analysis suggested that H. pylori infections might be associated with PD risk (Shen et al, 2017). When compared to H. pylori-negative PD patients, H. pyloriinfected PD patients present with worse motor dysfunction and they display a 12-fold increase in mortality rate (McGee et al, 2018;Zendehdel and Roham, 2020). Additionally, H. pylori may affect the absorption of levodopa, and the eradication of H. pylori in PD patients has been shown to improve motor function and levodopa absorption compared with those in PD patients in whom H. pylori were not eradicated (McGee et al, 2018).…”
Section: Altered Gastrointestinal Microbiota Composition In Pdmentioning
confidence: 99%
“…A meta-analysis suggested that H. pylori infections might be associated with PD risk (Shen et al, 2017). When compared to H. pylori-negative PD patients, H. pyloriinfected PD patients present with worse motor dysfunction and they display a 12-fold increase in mortality rate (McGee et al, 2018;Zendehdel and Roham, 2020). Additionally, H. pylori may affect the absorption of levodopa, and the eradication of H. pylori in PD patients has been shown to improve motor function and levodopa absorption compared with those in PD patients in whom H. pylori were not eradicated (McGee et al, 2018).…”
Section: Altered Gastrointestinal Microbiota Composition In Pdmentioning
confidence: 99%
“…In recent years numerous reviews focused on this topic [ 11 , 13 , 14 , 68 , 79 , 331 , 332 , 333 , 334 , 335 , 336 , 337 , 338 , 339 , 340 , 341 , 342 , 343 , 344 , 345 , 346 ]. Most of HPI–linked extra-gastroduodenal chronic diseases and disorders as well as treatments used for are known to increase risk of OP, falls and OFs, especially in the elderly [ 317 , 347 , 348 , 349 ]. More than 80% of patients with a clinical vertebral or non-vertebral fracture suffer at least one chronic disease, and in 65.5% of these patients at least one bone- and/or fall-related RF was found [ 350 ].…”
Section: Hpi-associated Chronic Extra-gastroduodenal Diseases Medmentioning
confidence: 99%
“…UTIs occur in 3% to 5% of girls and 1% of boys [ 2 ]. Studies have shown that the prevalence of UTIs is greater than that of bacterial meningitis, bacterial pneumonia, middle ear infection and bacteraemia [ 3 ]. During infancy, 5% of febrile girls and 20% of uncircumcised febrile boys present with UTI.…”
Section: Introductionmentioning
confidence: 99%